2020
DOI: 10.3389/fnhum.2019.00472
|View full text |Cite
|
Sign up to set email alerts
|

Glioma Migration Through the Corpus Callosum and the Brainstem Detected by Diffusion and Magnetic Resonance Imaging: Initial Findings

Abstract: Purpose: Glioma cell infiltration, in which the glioma tumor cells spread long distances from the primary location using white matter (WM) or blood vessels, is known as a significant challenge for surgery or localized chemotherapy and radiation therapy. Following the World Health Organization (WHO), the glioma grading system ranges from stages I to IV, in which lower-grade gliomas represent benign tumors, and higher grade gliomas are considered the most malignant. Materials and Methods: We gathered magnetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…Interestingly, the connectivity between the body and genu of the corpus callosum increased by 10-30% over 1 year (see Supplementary Figure 6). This extends our previous study on glioma invasion, which revealed that the corpus callosum body played a role in this procedure (Sharifi et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, the connectivity between the body and genu of the corpus callosum increased by 10-30% over 1 year (see Supplementary Figure 6). This extends our previous study on glioma invasion, which revealed that the corpus callosum body played a role in this procedure (Sharifi et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…31 main challenges in treating glioma (48). The corpus callosum serves as a hub between hemispheres, and glial cells may migrate along the corpus callosum during glioma cell infiltration (49). Additionally, three regions were colocalized with stroke, including 10q24.33, 9p21.3, and 2q33.2 (50) (Fig.…”
Section: Concordance With Previous Gwasmentioning
confidence: 99%
“…Another interesting study by Kakita et al revealed the migration of labeled glial progenitors from the neonatal SVZ through the corpus callosum to the contralateral hemispheres, which correlates with the pattern of migration described by Kroonen et al (45,69). More recently, diffusion and magnetic resonance performed on seven glioma and six control patients showed that the human corpus callosum also act as a GBM cell migration track (70). In children, Caretti et al analyzed a series of autopsies from 16 patients with DMG and observed that tumoral cells spread to the SVZ in 63% of the cases (19).…”
Section: Glioma Stem Cells Take Different Routes To Reach the Subventricular Zonementioning
confidence: 52%
“…( 45 , 69 ). More recently, diffusion and magnetic resonance performed on seven glioma and six control patients showed that the human corpus callosum also act as a GBM cell migration track ( 70 ). In children, Caretti et al.…”
Section: Glioma Stem Cells Share Features With Neural Stem Cellsmentioning
confidence: 99%